Toward A Christian Transformational Leadership - Avi Christian; Lely Natalia; Joni A. Bangun; Siti Hadijah (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
Transformational leadership is a theory of leadership that has gained profound interest among scholars for decades. Compared to transactional leadership that emphasizes reward and punishment, transformational leadership style has focused more on the inner development of the followers. A leader with transformational leadership style would seek to stimulate his or her followers intellectually, so the transformation of the organization would start with the change of perception of the people. This article argues further that a Christian perspective could enrich the prominent theory of transformational leadership by placing Christ as the center of inspiration and God’s transformative power as the primary motivation to contribute toward the broader society. A Christian transformational leadership emphasizes God as the source of transformation and perceive the ability of the Christian leader to transforms the people as a horizontal expression of God’s transformative power experienced by the Christian leader. In other words, inner transformation leads toward the transformation of the world outside.